2004
DOI: 10.1002/cne.20378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between δ‐opioid receptor functional response and autoradiographic labeling in rat brain and spinal cord

Abstract: The distribution of delta-opioid receptors (DORs) in the rat central nervous system has been previously characterized by radioligand binding and immunohistochemistry. However, the functional neuroanatomy of DORs has not been mapped in any detail; this is potentially important, because these receptors appear to be primarily cytosolic. Opioid receptors can couple to G(i/o) G proteins, a process that is detected by agonist-stimulated [35S]guanylyl-5'-O-(gamma-thio)-triphosphate ([35S]GTPgammaS) binding. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 55 publications
5
26
0
Order By: Relevance
“…Moreover, immunocytochemistry analysis revealed that the majority of Kir3.1 and Kir3.2 subunits were present in nonpeptidergic small size afferents (Chung et al, 2014), which also express DOPr (Bardoni et al, 2014). The postsynaptic distribution of Kir3.1/3.2 subunits in lamina IIo of the spinal dorsal horn (Marker et al, 2005) is similarly consistent with DOPr expression, as visualized by autoradiography (Pradhan and Clarke, 2005) and in DOPr-GFP-expressing mice ). In keeping with this distribution, analgesia by intrathecal administration of deltorphin II was reduced in tertiapin Q-treated mice and in mice lacking either Kir3.1 or Kir3.2 subunits (Marker et al, 2005).…”
Section: D-opioid Receptors and Activation Of G Protein-coupled Inmentioning
confidence: 54%
“…Moreover, immunocytochemistry analysis revealed that the majority of Kir3.1 and Kir3.2 subunits were present in nonpeptidergic small size afferents (Chung et al, 2014), which also express DOPr (Bardoni et al, 2014). The postsynaptic distribution of Kir3.1/3.2 subunits in lamina IIo of the spinal dorsal horn (Marker et al, 2005) is similarly consistent with DOPr expression, as visualized by autoradiography (Pradhan and Clarke, 2005) and in DOPr-GFP-expressing mice ). In keeping with this distribution, analgesia by intrathecal administration of deltorphin II was reduced in tertiapin Q-treated mice and in mice lacking either Kir3.1 or Kir3.2 subunits (Marker et al, 2005).…”
Section: D-opioid Receptors and Activation Of G Protein-coupled Inmentioning
confidence: 54%
“…However, significant stimulation was obtained in the striatum, which served as a positive control. Pradhan and Clarke (2005) similarly identified only negligible binding of [ 125 I]DELT, which has higher specific activity, and virtually no stimulation of [ 3 H]GTP␥S binding by DELT in the RVM of naive rats. Unfortunately, methods offering greater anatomical resolution proved unworkable in the RVM.…”
Section: Discussionmentioning
confidence: 90%
“…It is interesting to speculate as to why differences among agonists can be observed. It is known, for example, that different agonists can differentially traffic the receptor (Pradhan and Clarke, 2005;Pradhan et al, 2009Pradhan et al, , 2010 and that different agonists can signal differentially, as suggested by the appearance of pharmacologic subtypes of the receptor. It is possible that these and other mechanisms can contribute to agonists' differences.…”
Section: Discussionmentioning
confidence: 99%
“…All of the compounds shown have been described as full ␦-opioid receptor agonists but nevertheless can have some important differences in their pharmacologies. For example, SNC-80 (4-[(R)-[(2S,5R)-4-allyl-2,5-dimethyl-piperazin-1-yl]-(3-methoxyphenyl)methyl]-N,N-diethyl-benzamide) has been shown to reliably stimulate locomotor activity and to produce convulsions in a number of preclinical species (Broom et al, 2002a;Jutkiewicz et al, 2005), whereas there have been no reports of either seizure activity or alteration in locomotor activity with AR-M100390 (N,N-diethyl-4-[phenyl(piperidin-4-ylidene)methyl]benzamide) (Pradhan and Clarke, 2005;Smagin et al, 2008;T. Hudzik, unpublished observations), which may represent the opposite end of the spectrum of activity.…”
Section: Introductionmentioning
confidence: 99%